Parcerias de desenvolvimento produtivo vinculadas ao complexo industrial da saúde: um estudo sobre os avanços e o papel de cada agente de saúde na inovação e estruturação do Parque Farmacêutico Nacional - Vitor de Menezes Pimentel (2012)
This paper focuses on the Product Development Partnership (PDP) of the pharma and drugs sector and aims to evaluate the Productive Development Policy, which was implemented nationwide in Brazil in 2008 within the context of the Health Industrial Complex. This evaluation arises due to the importance of the pharmaceutical industry - which currently experiences a trade deficit of around 12 billion dollars - for the development of the Brazilian economy and the welfare of its population. To evaluate the PDP, several representatives of Governmental Agencies, Associations, Funding Agencies, Public and Private Pharmaceutical Laboratories and Fine Chemical Producers, were approached and presented each with a survey. The opinion of each participant was used to determine their role and contribution to this policy. The consensus opinion was that the Brazilian State should use its purchasing power to strengthen the national pharmaceutical industry. It was also consensual, for both private and public companies, that regulatory and tax-related bureaucracy complicates the functioning of these partnerships; for example, in the past four years, out of 32 officially authorised partnerships, only 6 have achieved product supply to the Brazilian Ministry of Health. Furthermore, the respondents felt greater coordination between the actors of this partnership is currently necessary. Specifically, greater efficiency within the Brazilian government bodies, and a greater integration with the private sector are imperative. While these are all important issues, they are actually underexplored and little discussed within the Brazilian health sector.